Agrarian Marxism. Issue 5 (19th September 2018) - Levien, Michael; Watts, Michael; Yan, Hairong
ABSTRACT: The purpose of this special issue is to advance heterodox reconstructions of agrarian Marxism on the occasion of Marx's 200th birth anniversary. Scholarship on the origins of agrarian capitalism and the contrasts between agrarian and industrial capitalism have been a vital part of debates over and within Marxism for more than a century and have been central to the social scientific and historical understandings of the modern world system. At the same time, since the seminal debates associated with the 'classical agrarian question, ' agrarian studies is marked by durable tensions and polarities in theoretical approach. While Marxists have long criticized 'populists' for ignoring capitalism and class, populists have charged Marxists with historical determinism. It is the premise of this special issue that much of this debate has reached something of an impasse. This is in part because new empirical work addressing the complex contemporary patterns and conjunctures of global agrarian capitalism, and because new and generative theoretical reconstructions of Marxism itself, offer exciting new horizons. Contributions to this special issue help point the way beyond this impasse, and illustrate that agrarian Marxism remains a dynamic theoretical program that offers powerful insights into agrarian change and politics in the twenty-first century.